Fool's gold: The return on investment in global mining, 1869-1969 - Klas Rönnbäck; Oskar Broberg; Dimitrios Theodoridis (The Journal of European Economic History (JEEH), 2022)
In this paper, we study the return on investments in mining for a whole century, starting in the "Golden Age" of resource exploitation in the late nineteenth century. We use a sample of more than 1,000 mining companies, registered on the London Stock Exchange 1869- 1969, but operating on all continents of the world. Our results suggest that the return on investments in mining was lower than for a comparable portfolio of all equity on the London Stock Exchange. Our results also suggest substantial differences in return depending on the type of resource mined - with diamond-stocks being particularly lucrative for investors and gold-stocks underperforming in the long run. At the same time, mining was a risky investment, when measured as volatility. Hence, our results fits badly with standard financial market theories of the relationship between risk and return. Instead, a combination of information asymmetries and a recurrent overoptimistic risk-appetite should be sought as potential explanations for investors' decisions and the return on investment in global mining.
Keywords: 330; Gold mining; Return on investment; Goldbergbau; Return on Investment; Welt